2023
DOI: 10.3390/fermentation9010046
|View full text |Cite
|
Sign up to set email alerts
|

Succinic Acid Production from Oil Palm Biomass: A Prospective Plastic Pollution Solution

Abstract: Plastic pollution has placed a significant emphasis on the need for synthesising bioplastics, such as polybutylene succinate (PBS), which is derived from succinic acid. Furthermore, environmental concerns and the depletion of non-renewable fossil fuels have initiated an interest in exploring the biotechnological route of succinic acid production via fermentation. Consequently, oil palm biomass might be a prospective substitute for the costlier pure carbon source, which is more sustainable and cost-effective du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
(142 reference statements)
0
0
0
Order By: Relevance
“…Recent research reported the ability to synthesize SA using xylose-rich hemicellulosic fractions from olive pits and sugarcane bagasse of A. succinogenes (yield from 28 to 34 g L −1 and 0.27 g g −1 ) [28]. Oil palm biomass has been studied as a carbon source for SA production by various strains of A. succinogenes [7]. However, the yields can vary depending on the treatments applied to the biomass and the fermentation conditions [7].…”
Section: Fermentation Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research reported the ability to synthesize SA using xylose-rich hemicellulosic fractions from olive pits and sugarcane bagasse of A. succinogenes (yield from 28 to 34 g L −1 and 0.27 g g −1 ) [28]. Oil palm biomass has been studied as a carbon source for SA production by various strains of A. succinogenes [7]. However, the yields can vary depending on the treatments applied to the biomass and the fermentation conditions [7].…”
Section: Fermentation Trialmentioning
confidence: 99%
“…Oil palm biomass has been studied as a carbon source for SA production by various strains of A. succinogenes [7]. However, the yields can vary depending on the treatments applied to the biomass and the fermentation conditions [7]. These recent studies highlighted the potential of additional low-cost sources for succinic acid production.…”
Section: Fermentation Trialmentioning
confidence: 99%
See 1 more Smart Citation